Multivariate GNSS attitude integrity: The role of affine constraints - Giorgi, G.; Teunissen, Peter (2016)
In this work we analyze the integrity properties of an affine-constrained estimator applied to arrays of GNSS antennas. GNSS pseudorange and carrier phase measurements from multiple antennas whose relative positions are known are cast in a linearly-constrained observation model. The linear constraints are inherent to an affine transformation that is applied to the baseline coordinates. The affine transformation yields enhanced redundancy, thus improving the model integrity properties with respect to the unconstrained model. The extent of the improvement is measured in terms of internal and external reliability.